Analytical Pricing Formulas for Hybrid Variance Swaps with Regime-Switching - Roslan, Teh Raihana Nazirah; Cao, Jiling; Zhang, Wenjun (2017)
The problem of pricing discretely-sampled variance swaps under stochastic volatility, stochastic interest rate and regimeswitchin" e is beine considered in this oaoer. An extension of the Heston stochastic volatiliw model structure is done bv adding the - . . . Cox-lngersoll-Row (CIR) ctochawc intereel rare modcl In add~uon[,h e parameme of the mndel are perm~rtedlo have uan<luonc followane a Markov cham proccrs whtch I, conunuous and &>.uvcrable lh~shb bnd model cdn be uced lo tllusunre ccrrlrn macmec~nomicc onditions.-for example the changing phases of business stages. The outcome of our regime-switching hybrid model is presented in lerms of analytical pricing formulas for variance swaps.